Toward a science of consciousness III : the third Tucson discussions and debates - Hameroff, Stuart R.; Kaszniak, Alfred W., 1949-; Chalmers, David John, 1966- (Complex adaptive systems., 1999)
"Can there be a science of consciousness? This issue has been the focus of three landmark conferences sponsored by the University of Arizona in Tucson. This volume presents a selection of invited papers from the third conference. It showcases recent progress in this maturing field by researchers from philosophy, neuroscience, cognitive psychology, phenomenology, and physics."--Jacket